Effect of mindfulness on psychological distress, emotion regulation and marital satisfaction - Mohammad Gholami Fesharaki, Abdollah Omidi, Fatemeh Forouzesh Yekta, Hamid Yaghubi, Fereshteh Mootabi, Rasol Roshan, (Opción, 2019)
The aim of the present research was to study the effect of mindfulness-based stress reduction program on psychological distress, emotion regulation and enhancement of marital satisfaction in women via the quasi-experimental method with pretest-posttest-follow up design with the control group. Results demonstrated that a mindfulness-based stress reduction program had an influence on the improvement of psychological distress (F=8.65, p<0.01), emotion regulation (F=31.39, p<0.0001) and marital satisfaction (F=19.92, p<0.0001) in married women. In conclusion, Mindfulness training may have beneficial effects for couple therapy and relationship enhancement as well as the psychological distress and emotion regulation.